Characteristics and effects of physical exercise programs for older cancer survivors: A scoping review (Características y efectos de los programas de ejercicio físico para personas mayores sobrevivientes de cáncer: Una revisión de alcance) - Igor Cigarroa; Estefanía Díaz; Constanza Ortiz; Raquel Otero; Irene Cantarero; Fanny Petermann-Rocha; Solange Parra-Soto; Rafael Zapata-Lamana; David Toloza-Ramírez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
There is a discrepancy about the characteristics and effects of exercise-based programs in older cancer survivors (OCS). Therefore, this scoping review aimed to identify the characteristics and effects of physical activity programs in OCS health. This scoping review followed the PRISMA guidelines and included randomized clinical trials and clinical trials from MEDLINE by PubMed, Scopus, Scielo, and PEDro, published between 2010 and 2020. Results suggest that physical programs were carried out in health centers (54.2%) and were based on physical exercise (74.4%). The length of the exercise interventions was between 3–6 months (87.5%) was performed 2–3 times per week (73.1%) with a duration between 20–60 minutes (78.2%) and was run by health professionals (94.4%). The health outcomes with the most positive effects were physical activity, depression, and quality of life. In conclusion, physical programs for OCS based on aerobic exercises are safe and could be a therapeutic strategy to improve different health markers in OCS.